OPTIMAL CONCENTRATION OF KANAMYCIN AS A SELECTIVE AGENT FOR THE TRANSFORMATION OF Musa cv. “GRAND NAIN” - Chi-Manzanero, BH; Acereto-Escoffié, POM; Castaño, E; Rodríguez-Zapata, LC (Ecosistemas y Recursos Agropecuarios, 2014)
The effect of different kanamycin concentrations on the growth and morphogenesis of meristematic tissue in the banana “Grand Nain” is presented in this study. The results obtained allowed us to establish the kanamycin concentration to be used for the selection of explants transformed by the nptII gene. This result will allow us to select the banana explants transformed by the integration of the nptII gene.
Keywords: Kanamycin; Musa; meristematic tissue